Architecture of Atwood Machine Props with Sensor-based Passive Infrared - Dandan Luhur Saraswati; Delia Achadina Putri (Universitas Ahmad Dahlan, 2018)
The aim of this research is to develop Atwood machine propswith sensor-based PIR (Passive Infrared) to determine the acceleration value of earth gravity. This type of research is an experiment conducted in the physics laboratory of Universitas Indraprasta PGRI. Atwood machine was developed by using PIR (Passive Infrared) sensors to detect the movement of the objects used. Based on the trialof the result of the data analysis experiment tool, the acceleration of gravity was obtained (9.87 ± 0.08) m/s2. Whereas the value of acceleration of gravity in the literature is 9,80665 m/s2. The obtained results shows that the acceleration of gravity obtained in this research is not much different from the acceleration value of gravity found in the literature so that Atwood machine tool that is developed by using PIR sensor is recommended to be one alternative tool in determining the acceleration of earth gravity.